EMOTIONAL BRAND ATTACHMENT AND BRAN LOVE MEDIATE SATISFACTION TO LOYALTY ON PRODUCT LAPTOP - Ayu Laras Wati; Sri Vandayuli Riorini (Business, Economics dan Entrepreneurship, 2023)
The Covid-19 pandemic requires all activities to be carried out at home. This makes a laptop electronic device a tool to support daily activities during the Covid-1 pandemic. This study offers a research model in the form of the role of emotional brand attachment and brand love on brand satisfaction in brand loyalty through an implicit model analyzed by Structural Equation Modeling (SEM). This study aims to (1) determine the effect of brand satisfaction on brand loyalty, (2) determine the effect of brand satisfaction on emotional brand attachment, (3) determine the effect of brand satisfaction on brand love, in addition (3) determine the effect of emotional brand attachment on brand love , (4) knowing the effect of emotional brand attachment on brand loyalty, and (5) knowing the effect of brand love on brand loyalty. In the results of this study there are 4 hypotheses accepted and 2 hypotheses rejected.